The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/1980-5373-mr-2017-1070
|View full text |Cite
|
Sign up to set email alerts
|

Submerged Friction Stir Welding of 6061-T6 Aluminium Alloy under Different Water Heads

Abstract: The aim of this paper is to determine the feasibility of submerged friction stir welding of 6061-T6 aluminium alloy on different water heads through macrostructuralanalysis.In this work, aluminium 6061-T6 alloy was friction stir welded under normal and submerged conditions at different rotational speeds of 400 rpm, 800 rpm, 1200 rpm, 1600 rpm. The water head was varied from 10 to 30 mm in the case of thesubmerged friction stir welding process. In both normal and submerged friction stir welding processes, a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
2
2
0
1
Order By: Relevance
“…The increase in the tensile strength and percentage elongation correlates with the microstructural grain sizes. Similar studies where the application of submerged multiple pass SFSP increased UTS were reported in the literature [23,[35][36][37].…”
Section: Tensile Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…The increase in the tensile strength and percentage elongation correlates with the microstructural grain sizes. Similar studies where the application of submerged multiple pass SFSP increased UTS were reported in the literature [23,[35][36][37].…”
Section: Tensile Propertiessupporting
confidence: 82%
“…The fourth SFSPed pass resulted in a very fine homogeneous grain structure. Similar work including the application of multiple pass SFSP was reported in the literature [34][35][36].…”
Section: Microstructural Analysissupporting
confidence: 62%
“…In the role of higher rotation speed and traverse speed, the weld center temperature may reach the solid solution temperature of aluminum alloy, so that the Mg 2 Si reinforcing term particles dissolved in the α-Al matrix and the nucleation effect on the grain boundaries is weakened, resulting in abnormal grain growth in the welding process. According to the research of Rathinasuriyan et al [26], excessive welding heat input in friction stir welding leads to turbulent flow in the weld fusion zone, thus promoting the formation of defects. Figure 11 shows different rotation speeds and traverse speeds under the influence of grain boundary content.…”
Section: Macro-and Microstructurementioning
confidence: 99%
“…Gambar 7 menunjukan perbandingan besar daerah lasan berdasarkan perbedaan besar diameter pin pada tool, dimana semakin besar diameter pin maka akan semakin besar pula daerah lasan. Penelitian ini juga menujukkan struktur makro akibat pengadukan logam yang berbentuk onion ring seperti pada penelitian R. Chandran [20]. Semakin besar diameter pin pada tool maka daerah lasan akan semakin besar.…”
Section: Analisis Cacat Dan Struktur Makrounclassified